Kajian Ekonomi dan Kesejahteraan Petani Karet Desa Sirih Sekapur Kecamatan Jujuhan Kabupaten Muaro Bungo - Rogayah, Rogayah; Alawiyah, Wiwin (Universitas Batangahari Jambi, 2024)
This research aims to determine the description of rubber farmers' farming activities, analyze farmers' income and analyze the level of welfare of rubber farmers in Sirih Sekapur Village, Jujuhan District, Bungo Regency. The data analysis method used in this research is quantitative descriptive analysis. Sampling in this study was carried out using simple random sampling, namely by taking a sample of 15% of the total population of 270 RTP so that the total sample in this study was 41 RTP. Data collection techniques include observation, interviews and documentation directly in the field. The results show that the average total cost incurred by farmers in Sirih Sekapur Village is IDR 1,939,868/Ha/Month and they receive an income of IDR 6,014,634/Ha/Month, resulting in an income of IDR 4,074,766/Ha/Month. Meanwhile, the welfare of rubber farmers is obtained using Farmer Exchange Rate (NTP) analysis with the average consumption expenditure of farmer households amounting to IDR. 3,960,600/Ha/Month and an average revenue of Rp. 6,014,634/Ha/Month, resulting in an average Farmer Exchange Rate of 151%, which means NTP> 100, which indicates that the level of welfare of rubber farmers in Sirih Sekapur Village classified as high (prosperous).